Obama's Wars : The Inside Story - Woodward, Bob (GHQ, Rawalpindi Services Book Club, 2011)
In Obama's Wars, Bob Woodward provides the most intimate and sweeping portrait yet of the young president as commander in chief. Drawing on internal memos, classified documents, meeting notes and hundreds of hours of interviews with most of the key players, including the president, Woodward tells the inside story of Obama making the critical decisions on the Afghanistan War, the secret campaign in Pakistan and the worldwide fight against terrorism. Woodward has discovered how the Obama White House really works, showing that even more rough decisions lie ahead for the cerebral and engaged president. Obama's Wars offers the reader a stunning, you-are-there account of the president, his White House aides, military leaders, diplomats and intelligence chiefs in this time of turmoil and danger.
Include Index, Glossary and Illustrations
Keywords: Obama, Barack -- Obama, Barack -- Military Leadership